Response from Salva Shariq, et al. (J Pak Med Assoc. 2024; 74: 602) The potential of methylene blue in treating septic shock: is it worth a shot? - Salva Shariq; Areej Khawaja; Nima Khowaja (Journal of the Pakistan Medical Association, 2024)
We appreciate the thoughtful engagement with our letter discussing the potential of methylene blue (MB) in treating septic shock. It is crucial to address the concerns raised regarding the evidence supporting the use of MB in this context. As rightly pointed out, the cornerstone of septic shock management involves early administration of appropriate antibiotics and fluid resuscitation, which we emphasized in our original letter. These interventions remain fundamental and should be promptly initiated in clinical practice. Continue..